Destabilization of Immersed Dense Granular Material Submitted to Localized Fluidization: An Experimental and Numerical Study - Aboubacar Sidiki Dramé; Li Wang; Yanping Zhang (Journal of Spectroscopy)
An alternative experimental approach and a numerical analysis for the study of destabilization by localized fluidization of an immersed dense granular material are presented. To visualize the evolutions of the internal structure of the granular medium, the hydrogel beads, composed of about 99% of water and having substantially the same refraction indexes, are used as solid phase. A LED lighting system is used in place of a laser lighting system. As a result, the optical access restriction of porous structure is removed. A real economic alternative for the experimental study of fluid-grain coupling during destabilization by localized fluidization of a granular material is created. The experimental phenomenology presented in the literature is verified: the system passes successively through three different stationary regimes: static regime, fluidized cavity regime, and fluidized chimney regime. Some restrictions of using hydrogel beads as particles in the study of liquid-solid interaction are also discussed.